PENGARUH ISLAMIC BRANDING DAN CITRA BANK SYARIAH TERHADAP MINAT NASABAH MELAKUKAN TRANSAKSI DI BANK SYARIAH (STUDI KASUS PT. BPRS PUDUARTA INSANI) - Dwi Rama Syahri; Dahrani (JURNAL ILMIAH EDUNOMIKA, 2025)
This research aims to determine the influence of Islamic branding and image of sharia banks on customers' interest in carrying out transactions at sharia banks (case study of PT. BPRS Puduarta Insani). This research is research that uses a quantitative approach. The research instrument is a questionnaire with a type of analysis model that uses multiple linear regression. The population in this study were all customers of the Puduarta Insani Sharia People's Financing Bank (BPRS), totaling 4,270 people with a sample of 98. Meanwhile, data collection techniques used questionnaires and observation. The data analysis technique in this research is multiple regression analysis using SPSS software. The research results show that Islamic Branding has a positive and significant influence on customer interest in carrying out transactions, Citra Bank Syariah does not have a significant influence in increasing customer interest, and simultaneously, Islamic Branding and Citra Bank Syariah have a significant impact on customer interest. Keywords: Islamic Branding, Sharia Bank Image, Customer Interest